2015
DOI: 10.1515/ama-2015-0021
|View full text |Cite
|
Sign up to set email alerts
|

Application Of CFD To Modeling Of Squeeze Mode Magnetorheological Dampers

Abstract: The so-called squeeze flow involves a magnetorheological (MR) fluid sandwiched between two planar surfaces setting up a flow channel. The height of the channel varies according to a prescribed displacement or force profile. When exposed to a magnetic field of sufficient strength MR fluids develop a yield stress. In squeeze-mode devices the yield stress varies with both the magnetic field magnitude and the channel height. In this paper an unsteady flow model of an MR fluid in squeeze mode is proposed. The model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 13 publications
(9 reference statements)
0
16
0
Order By: Relevance
“…Both of the three-dimensional numerical simulation and experimental results demonstrated that the air leakage of a circular cooler was solvable effectively with the magnetorheological fluid seal method. Gołdasz and Sapinski (2015) studied a squeeze mode MR damper with a CFD model, and the well-known fact was confirmed that the compressive loads increase with the decreasing gap height.…”
Section: Introductionmentioning
confidence: 79%
“…Both of the three-dimensional numerical simulation and experimental results demonstrated that the air leakage of a circular cooler was solvable effectively with the magnetorheological fluid seal method. Gołdasz and Sapinski (2015) studied a squeeze mode MR damper with a CFD model, and the well-known fact was confirmed that the compressive loads increase with the decreasing gap height.…”
Section: Introductionmentioning
confidence: 79%
“…Table 4 also shows whether the presented models are one-way, two-way, or non-coupled models. The one-way coupling techniques are shown to be adopted in FEM-based magnetic field simulation coupled with FVM-based flow analysis, as shown by Elsaady et al (2020), Gołdasz and Sapiński (2015a), Gurubasavaraju et al (2018a, 2018b), Meng et al (2017), Parlak and Engin (2012) and Parlak et al (2012). The two-way coupled solutions are often to be performed by COMSOL/Multiphysics in which the AD/DC module is used for magnetic field simulation, whereas the fluid flow and heat transfer modules are used for fluid flow solution, as shown by Bompos and Nikolakopoulos (2011), Case et al (2013, 2014), Guo and Xie (2019), Li et al (2019b), Omidbeygi and Hashemabadi (2013), Wang et al (2017) and Zheng et al (2014, 2015, 2017).…”
Section: Reviewing Research Efforts On Modelling Mr Fluid Devices mentioning
confidence: 99%
“…Research on flow of MR fluids in squeeze and pinch modes, described by Figure 2(c) and (d), respectively, is quite rare (Sapinski and Gołdasz, 2018). The flow characteristics of these modes are thought to be not fully predicted (Gołdasz and Sapiński, 2015a; Gołdasz et al, 2018). Employment of squeeze mode in MR fluid devices, either being standalone or merged with the shear mode is found to conduce higher performance of MR devices (Farjoud et al, 2011; Lee et al, 2019; Wang et al, 2019).…”
Section: Numerical Approaches Applied For Mr Applications Other Thmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhou and Bai [25] conducted a three-dimensional (3D) numerical FEM analysis for MRF seal technology applied on a circular cooler. By defining the apparent viscosity as the ratio of the fluid's yield stress over the local shear rate, Gołdasz and Sapiński [26] studied a squeeze mode MR damper with a CFD model, and the well-known fact was confirmed that the compressive loads increase with the decreasing gap height. More recently, using the finite volume method on a two-dimensional moving grid, Syrakos et al [27] successfully captured the hysteresis of a damper caused by the inertia of fluid under high-frequency loadings.…”
Section: Introductionmentioning
confidence: 99%